NILAI-NILAI KERJA KERAS (KREATIF, RAJIN, ULET, TELITI, TEKUN, KOMITMEN, DISIPLIN DAN BERILMU) DAN CINTA TANAH AIR DALAM ISLAM - Fitri Umami , Idail Uzmi; Sobri, Muhammad (LP2M Institut Agama Islam Nurul Hakim, 2022)
Character education is indeed being echoed by the government lately, due to the emergence of problems with juvenile delinquency cases that often color the mass media, ranging from drug cases, free sex to brawls to the warmest case yesterday, namely a student killing his teacher. So that character education is included in the national education curriculum even though its implementation has not been maximized. One of the character education that needs to be formed and grown in children is the character value of hard work and love for the homeland. The value of hard work needs to be taught to children and young people so that they can appreciate every struggle of their parents who seek sustenance for them so that they become more diligent in studying, devoted and so on. Likewise, love for the homeland is no less urgent, especially now that Indonesia is being threatened with the issue of division due to Indonesia's diversity which consists of various ethnicities, races and religions. Therefore, this love for the homeland needs to be instilled into the next generation as the pillar of the nation's successor relay